SOSIALISASI PENYAKIT RABIES PADA SISWA SLTA DI DESA BEBANDEM KARANGASEM - N. S., Dharmawan.; Damriyasa, I M.; Ardana, I. B. K.; Kendran, A. A. S.; Agustina, K. K. (Buletin Udayana Mengabdi, 2012)
This Community Service was conducted on October 23rd. 2010 in Bebandem village, Karangasem regency in the form of socialization of rabies on senior high school students. The aim of this program was to give knowledge, clinical symptoms, transmission, and prevention of the rabies diseases. There were 50 participants who came from representatives of each class. Twenty-eight (56%) participants reported that at their house, they have dogs and cats, mostly (50%) have not been vaccinated. The activity runs smoothly and as planned. Socialization of rabies diseases has improved the understanding of all participants. At the end of the event, most of them (90%) reported that they were satisfied and there are 48 (96%) participants are interested in becoming a volunteer to join to inform rabies to other school children.